EFL Students’ Perception of Using Youtube Videos To Effect Their Communicative Competence - Amanda Amanda; Syamsu Tang; Sam Hermansyah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
This research uses descriptive qualitative method as the research methodology. This research is conducted to Identify EFL students‘ views on the use of YouTube videos in learning and Assess the extent to which the use of YouTube videos affects EFL students’ communicative competence.The purpose of this study is to find out how students view the use of YouTube videos to improve communicative competence, which this study will focus on UMS Rappang (University of Muhammadiyah Sidenreng Rappang) students majoring in English language education semester four in the year 2024, 38 students’ as the main population who will be the subject of research.The findings from this study show that it can be concluded that YouTube is very impactful in improving students' communicative competence. The respondents of this study use YouTube mainly for English language learning, and they prefer the video platform that is YouTube application because of its visual and auditory elements, accessibility, and convenience as well as its long duration and can also be accessed anytime and anywhere.